1986
DOI: 10.1093/nar/14.8.3229
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sense regions in satellite RNA of cucumber mosaic virus form stable complexes with the viral coat protein gene

Abstract: The interaction in vitro of the RNA of the Q-strain of cucumber mosaic virus (CMV) with its satellite RNA (sat-RNA) has been studied. In hybridisation reactions containing 30% formamide at 45 degrees, sat-RNA binds to CMV RNA 3 and 4 but not to CMV RNA 1 and 2 or RNA from tobacco mosaic virus and alfalfa mosaic virus. The viral coat protein gene present in RNA 3 and 4 contains the site of binding but this region does not contain complementary sequences of any significant length to the sat-RNA sequence. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
2
Order By: Relevance
“…In vitro binding studies, however, detected stable complexes between satellite RNA and Q-CMV RNAs 3 and 4 (166). Therefore it has been suggested that CMV satellite RNA may regulate the expression of the coat protein gene from RNA 4 (166). However, using multiple strains of CMV and several CMV satellite RNAs, we were able to detect stable complexes involving CMV RNAs 2, 3, and 4 in various combinations, and none of these complexes inhibited the in vitro translation of coat protein from RNA 4 (40a).…”
Section: Alteration In Virus Titermentioning
confidence: 89%
“…In vitro binding studies, however, detected stable complexes between satellite RNA and Q-CMV RNAs 3 and 4 (166). Therefore it has been suggested that CMV satellite RNA may regulate the expression of the coat protein gene from RNA 4 (166). However, using multiple strains of CMV and several CMV satellite RNAs, we were able to detect stable complexes involving CMV RNAs 2, 3, and 4 in various combinations, and none of these complexes inhibited the in vitro translation of coat protein from RNA 4 (40a).…”
Section: Alteration In Virus Titermentioning
confidence: 89%
“…They do not exhibit any base sequence homology to the genomes of either virus or plant host, and they are replicated by the helper virus-coded RNA-dependent RNA polymerase. Evidence has been presented for a direct interaction of satellite and viral RNA (Rezaian and Symons, 1986), and for the attenuating activity of putative, satellite-encoded proteins (Owens and Kaper, 1977). In cases where the presence of satellite RNA attenuates the disease caused by the helper virus, satellite RNAs have been used as a biological control in crop protection, e.g.…”
Section: Transgenic Plants That Express Viral Satellite Rna Satellitementioning
confidence: 99%
“…2. Схема построения плазмиды, продуцирующей антисмысловые транскрипты ТК-гена вируса герпеса [11]. Fig.…”
unclassified
“…2. The construction diagram of recombinant plasmid coding for antisense RNA to HSV TK-gene [11]. единичной копии.…”
mentioning
confidence: 99%
See 1 more Smart Citation